Purificação de níquel a partir de soluções sulfúricas por extração por solventes utilizando-se Cyanex 272 e misturas de extratantes - Alexandre Silva Guimaraes (2014)
The purification of aqueous solutions simulating leach liquors of sulfuric acid lateritic ores containing calcium, cobalt, copper, magnesium, manganese, nickel and zinc employing the solvent extraction technique using the extractant Cyanex 272 and mixtures of Cyanex 272 with versatic acid, Cyanex 301, naphthenic acid, mixture of carboxylic acids (MAC) and D2EHPA, diluted in n-heptane, was investigated in the present work. The main objective was to develop an organic extraction system formed by combining suitable extractants aiming to obtain a liquor purity in conditions such that allow its direct routing to the nickel eletrodeposition step. The solvent extraction tests were carried out at 50°C maintaining the volume ratio of the aqueous and organic phases (A/O) at unit, and varying the conditions of acidity of the liquor in the pH range from 2 to 7 (the pre-treatment step of liquor, when solely Cyanex 272 was used as extractant), and from 3.8 to 7.0 (in the purification step of nickel, when mixtures of extractants were used). The liquor was pre-purified in relation to the metals Co, Cu, Mn and Zn at pH = 3.88 and 20%v/v Cyanex 272, so that remain in the raffinate about 98.5% nickel, 76% calcium and 64% magnesium. Potential extractants systems have been identified: versatic acid (10%v/v), naphthenic acid (10%v/v), MAC (5 and 10%v/v) and D2EHPA (5 and 10%v/v) mixed with Cyanex 272 (20%v/v), which were found to be susceptible to promote the purification of liquor to nickel against alkaline earth metals calcium and magnesium. The combination of 5%v/v D2EHPA with 20%v/v Cyanex 272, at pH 4.8, was identified as the most suitable for the purification of organic liquor extractor system for extracting preferably high levels of calcium (about 72%) and magnesium (about 60%) over nickel (extractions around 2%), thus allowing to obtain a raffinate stream with about 96% nickel that can be routed directly to step eletrodeposition.